Applicazioni del GPR per l’analisi degli intonaci di supporto a pitture murali: il caso studio della cappella Bardi a Firenze - Emanuele Marchetti (Restauro Archeologico)
In the framework of the Heritage Ground Penetrating Radar (HGPR) project, the Department of Earth Sciences of the University of Florence (DST) performed GPR measurements to investigate plasters supporting mural paintings. This study presents an acquisition approach of GPR data adapted to detect the subtle (cm) thickness of plasters, well below the standard GPR application. In order to increase the signal-to-noise ratio of GPR data we performed punctual measurements, with acquisition lasting at least 10 seconds in each point. Moreover the interpolation of 4 cm thick polystyrene level between the antenna and the wall, transparent to electromagnetic waves, allows to increase the time difference between subsequent reflections from the different levels, therefore improving our ability to identify shallow discontinuity positioned at depth well below the wavelength of the adopted signal. The methodology has been experimented in the Bardi Chapel in Florence, currently undergoing restoration activity.